Willems I and Willems II Methods for Dental Age Assessment in Children and Adolescents aged 3–16 years in the Varanasi Region: Applicability and Comparability - Mishra , R; Mourya , R; Srivastava , VK; Pandey, SK; Kumar, NPG (Journal of Indian Academy of Forensic Medicine, 2024)
In order to create new, simplified tables (Willems I method) for males and females in the Belgian Caucasian population, Willems G et al. (2001) reexamined Demirjian's technique. With these tables, dental age can be represented directly in years without the need for additional conversion tables. Using the prior data and a new study group, Willems G et al. (2010) created a common table for males and females to overcome cases of unknown gender and created a non-gender-specific method (Willems II method) that was not gender-specific. This study aims to evaluate the Willems I and Willems II methods for age estimation in a sample of the Varanasi region population. In this cross- sectional study, 432 samples (237 boys and 195 girls of age range 3–16 years) from the population of Varanasi region were evaluated to validate the Willems I and Willems II age estimation methods. A paired t-test was applied to determine the statistical significance between estimated dental age and chronological age. The Willems I method underestimated the dental age in boys by -0.27 ± 0.80 years and in girls by -0.60 ± 0.95 years. The Willems II method also underestimated the age by -0.57 ± 0.86 years in boys and -0.38 ± 0.93 years in girls. Pearson correlation revealed a strong positive association in both methods. The Willems I and Willems II methods are not exactly applicable, but the Willems I method is more relatable to the actual age of the boys sample and the Willems II method for the girls sample.
Keywords: Age estimation; Dental age; Tooth Development; Willems I method; Willems II method